The nature principle : reconnecting with life in a virtual age - Louv, Richard, ....- (Chapel Hill (N.C.) : Algonquin books of Chapel Hill, 2012)
For many of us, thinking about the future conjures up images of Cormac McCarthy's The Road: a post-apocalyptic dystopia stripped of nature. Richard Louv, author of the landmark bestseller Last Child in the Woods, urges us to change our vision of the future, suggesting that if we reconceive environmentalism and sustainability, they will evolve into a larger movement that will touch every part of society. This New Nature Movement taps into the restorative powers of the natural world to boost mental acuity and creativity; promote health and wellness; build smarter and more sustainable businesses, communities, and economies; and ultimately strengthen human bonds. Supported by groundbreaking research, anecdotal evidence, and compelling personal stories, Louv offers renewed optimism while challenging us to rethink the way we live.
Now with an updated feature on the New Nature Movement